Dynamical System Modulation for Robot Learning via Kinesthetic Demonstrations - Hersch, M.; Guenter, F.; Calinon, S.; Billard, A. (IEEE transactions on robotics, 2008)
We present a system for robust robot skill acquisition from kinesthetic demonstrations. This system allows a robot to learn a simple goal-directed gesture and correctly reproduce it despite changes in the initial conditions and perturbations in the environment. It combines a dynamical system control approach with tools of statistical learning theory and provides a solution to the inverse kinematics problem when dealing with a redundant manipulator. The system is validated on two experiments involving a humanoid robot: putting an object into a box and reaching for and grasping an object.